Clinical presentation of eating disorders in young males at a tertiary setting. Issue 1 (December 2015) - Shu, Chloe; Limburg, Karina; Harris, Chris; McCormack, Julie; Hoiles, Kimberley; Hamilton, Matthew; Watson, Hunna
Abstract Background Young males with eating disorders are a neglected study population in eating disorders. The aim of this study was to provide knowledge about the clinical presentation of eating disorders in young males. Methods The data source was the Helping to Outline Paediatric Eating Disorders (HOPE) Project (N 1000), a prospective, ongoing registry comprising consecutive paediatric (<18 years) tertiary eating disorder referrals. Young males with DSM-5 eating disorders (n = 53) were compared with young females with eating disorders (n = 704). Results There was no significant difference in the prevalence of diagnosis of bulimia nervosa (2 % vs 11 %, p = 0.26) among sexes. Males had comparable duration of illness (9 months;p = 0.28) and a significantly earlier age of onset (M = 12 years;p <0.001). Shape concern (2.39 vs 3.57, p <0.001) and weight concern (1.97 vs 3.09, p <0.001) were lower in males, and body mass indexz score (−1.61 vs −1.42, p = 0.29) and medical compromise (odds ratio [OR] = 0.64, 95 % CI: 0.36, 1.12) were comparable. Males had a two-folder higher odds of being diagnosed with unspecified feeding or eating disorders (40 % vs 22 % for females, p = 0.004). Driven exercise to control weight and shape was common and comparable in prevalence among males and females (51 % vs 47 %, p = 0.79) and males were less likely to present with self-induced vomiting (OR = 0.23, 95 % CI: 0.09, 0.59). Conclusion Boys with eating disorders are an understudied group with similarities and differences in clinical presentation from girls with eating disorders. Parents and physicians are encouraged to consider changes in weight, disturbed vital signs, and driven, frequent exercise for the purposes of controlling weight or shape, as possible signs of eating disorders among male children. Diagnostic classification, assessment instruments, conceptualisation, and treatment methods need to be refined to improve application to young males.